Peripheral Neutrophil to Lymphocyte Ratio Improves Prognostication in Colon Cancer - Rashtak, Shahrooz (Clin Colorectal Cancer, 2017)
BACKGROUND: We studied the role of peripheral Neutrophil to Lymphocyte Ratio (NLR) on survival outcomes in colon and rectal cancer to determine if its inclusion improved prognostication within existing staging systems. PATIENTS AND METHODS: Disease free and overall survival (DFS and OS) Hazard Ratios (HR) of pretreatment NLR were calculated for 2536 stage I-III colon or rectal cancer patients and adjusted for age, positive/total number of nodes, T stage, and grade. The association of NLR with clinicopathologic features and survival was evaluated and compared to American Joint Committee on cancer (AJCC) TNM staging and Memorial Sloan Kettering Cancer Center (MSKCC) models. RESULTS: High NLR was significantly associated with worse DFS (HR: 1.36 [95% CI 1.08–1.70] p: 0.009) and OS (HR: 1.65 [95%CI 1.29–2.10] p<0.0005) in all stages for colon, but not rectal cancer patients. High NLR was significantly associated with site-specific worse prognosis which was stronger in the left vs right colon; an inverse relationship with grade was found. The impact of high NLR on DFS and OS occurred early with the majority of deaths within 2 years following surgery. Adjusted HRs for 5-year and 2-year outcomes in colon cancer per each additional 2-unit increase in NLR were 1.15 (95% CI 1.08–1.23) and 1.20 (95% CI 1.10–1.30), respectively. Addition of NLR enhanced prognostic utility of TNM (TNM alone vs. TNM + NLR: C-index 0. 60 vs. 0.68), and MSKCC (MSKCC alone vs MSKCC + NLR: C-index 0.71 vs. 0.73) models for colon cancer patients. CONCLUSION: NLR is an independent prognostic variable for non-metastatic colon cancer that enhances existing clinical staging systems.